Thermoplastic elastomers manufactured of polymer blends - Rzymski, W. M.; Radusch, H. J. (Polimery, 2022)
Thermoplastic elastomers (TPE) constitute polymers combining properties of chemically cross-linked rubber with easy plastomer processing and recycling at certain temperatures (TPE). A review of publications on TPEs made of polymer blends s presented, covering thermoplastic elastomeric olefins (TPE-O), thermoplastic vulcanizates (TPE-V), melt-processible rubber(MPR) and thermoplastic elastomeric ionomers (TPE-EI). The atter constitute the newest group of TPEs, produced from lends of ionomeric plastomer with carboxylated or sulfonated ubber, interfacially cross-linked with metal oxides, with ormation of thermo-reversible aggregates and ion clusters.